T2-weighted cardiovascular magnetic resonance in acute cardiac disease - Eitel Ingo; Friedrich Matthias G (Journal of Cardiovascular Magnetic Resonance, 2011)
Abstract Cardiovascular magnetic resonance (CMR) using T2-weighted sequences can visualize myocardial edema. When compared to previous protocols, newer pulse sequences with substantially improved image quality have increased its clinical utility. The assessment of myocardial edema provides useful incremental diagnostic and prognostic information in a variety of clinical settings associated with acute myocardial injury. In patients with acute chest pain, T2-weighted CMR is able to identify acute or recent myocardial ischemic injury and has been employed to distinguish acute coronary syndrome (ACS) from non-ACS as well as acute from chronic myocardial infarction. T2-weighted CMR can also be used to determine the area at risk in reperfused and non-reperfused infarction. When combined with contrast-enhanced imaging, the salvaged area and thus the success of early coronary revascularization can be quantified. Strong evidence for the prognostic value of myocardial salvage has enabled its use as a primary endpoint in clinical trials. The present article reviews the current evidence and clinical applications for T2-weighted CMR in acute cardiac disease and gives an outlook on future developments. "The principle of all things is water" Thales of Miletus (624 BC - 546 BC)